Influence of Nurses' Empowerment on Quality Care: A comprehensive study of the literature - Ana Luiza Ferreira Aydogdu (ACHSM, 2024)
Background: The empowerment of nurses is a fundamental strategy for patient safety and consequently, for the success of health institutions.  This review aimed to identify in the scientific literature the influence of nurses' empowerment on the quality of care. Methods: An integrative review of literature, in which the PRISMA guidelines were followed, was completed. Articles were evaluated using the Joanna Briggs Institute (2020) Critical Appraisal Tools. The search for primary research articles was carried out in PubMed, Scopus, and Web of Science databases. Data were analyzed using content analysis methods. Results: Twelve studies were identified and included in this review. Three themes emerged: (1) the relationship between nurses' empowerment and quality of care; (2) opportunities and challenges of implementing empowerment in nursing; and (3) recommendations for the empowerment of nurses. Conclusion: Empowerment should be encouraged from college education and maintained in health institutions through continuing education and improvement of working conditions that allow nurses to provide efficient and effective care.